Blood Pressure and Hematoma Expansion in Hemorrhagic Stroke - Bikram Prasad Gajurel,; Pukar Ghimire,; Pradeep Panthee,; Sumit Shahi,; Rajeev Ojha,; Reema Rajbhandari,; Ragesh Karn, (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Hematoma expansion after hemorrhagic stroke can lead to devastating consequences. An important factor associated with this is high blood pressure. This study was carried out to find out what proportion of patients with hemorrhagic stroke develop hematoma expansion and whether blood pressure during presentation could be associated with it. Methods This prospective observational study was carried out over a period of one year in patients who were admitted with the diagnosis of hemorrhagic stroke. The collected data were entered into and analyzed by using the Statistical Package for the Social Sciences version 26 after obtaining approval from the Institutional Review Committee of the Institute of Medicine, Tribhuvan University. Results Out of 83 patients included in the study, history of hypertension was present in 72 (86.7%). Hematoma expansion occurred in 11 (13.3%). There was no statistically significant associations between mean systolic, diastolic, and mean blood pressures between patients with and without hematoma expansion [(168.9±35.6, 164.5±28.5, t(81)=0.47, p=0.64), (101.8±18.9, 101.2±19.6, t(81)=0.10, p=0.92) and (124.2±23.6, 122.3±21.5, t(81)=0.27, p=0.79) respectively (values in mmHg)]. Majority of patients with hematoma expansion had high absolute systolic blood pressure (27.3% vs 26.4%) and high absolute diastolic blood pressure (54.5% vs 38.9%); however, the associations were not statistically significant (p= 1.00 and 0.33 respectively). Conclusions High blood pressure is highly prevalent but hematoma expansion is not common in patients with hemorrhagic stroke. There was no statistically significant association between history of hypertension, gender, patient age, absolute and mean blood pressures, and hematoma expansion in our study.